2015
DOI: 10.1149/2.1031514jes
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Evaluation of a Micro-Tubular Solid Oxide Fuel Cell with an Inert Support Using Scandia-Stabilized Zirconia Electrolyte

Abstract: We have proposed a novel micro-tubular solid oxide fuel cell (SOFC) design with an inert support and an integrated current collector for the inner electrode to improve current collection efficiency as well as reduction-oxidation stability of the cell. In this work, a micro-tubular SOFC based on the proposed design was fabricated using scandia-stabilized zirconia (ScSZ) as electrolyte owing to its high ionic conductivity over a wide range of temperatures. Yttria-stabilized zirconia (YSZ), Ni, Ni-ScSZ, strontium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…9,20 Recently, yttria-stabilized zirconia (YSZ) was used as anode substrate to improve structural reliability of SOFCs. [21][22][23][24] It is noteworthy that anode electrode accounts for more than 90% materials used by the cell in anode-supported SOFCs. Therefore, the total material cost of anodesupported SOFC unit cell is largely dominated by the cost of anode electrode.…”
mentioning
confidence: 99%
“…9,20 Recently, yttria-stabilized zirconia (YSZ) was used as anode substrate to improve structural reliability of SOFCs. [21][22][23][24] It is noteworthy that anode electrode accounts for more than 90% materials used by the cell in anode-supported SOFCs. Therefore, the total material cost of anodesupported SOFC unit cell is largely dominated by the cost of anode electrode.…”
mentioning
confidence: 99%
“…In the recent decade, the inert substrate-supported SOFC has been considered as one of the most promising solutions to redox enhancement. The frequently used materials for inert substrate are zirconia-based ceramics due to the chemical compatibility and thermal expansion matching with other cell components. In the study of Panthi et al, the fabricated YSZ-supported microtubular SOFC exhibits promising tolerance toward the redox cycling with no apparent degradation after 10 redox cycles . Zhao et al also confirmed the satisfactory redox stability of YSZ-supported SOFC through 7–11 cycles without cell degradation or failure induced by electrolyte fracture. Compared to YSZ, the 3 mol % yttria stabilized zirconia (3Y-TZP) exhibits a much higher bending strength (1200 vs 279 MPa), which might be a more suitable material of choice for an inert substrate.…”
Section: Introductionmentioning
confidence: 99%
“…YSZ is a typical solid electrolyte that is widely studied due to its high phase stability and high ionic conductivity [2]. However, at intermediate temperatures (around 500 • C to 800 • C), it exhibits low ionic conductivity [4]. One promising solid electrolyte is the Sc-doped ZrO 2 (ScSZ) material system that shows higher ionic conductivity than YSZ at lower temperatures [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Only limited reports have been published on the combination of ScSZ with Ni as an electrode material. In SOFC mode, electrode materials using Ni and 10Sc1CeSZ:ZrO 2 [4], Ni/10 mol%Sc 2 O 3 -1 mol%Y 2 O 3 -stabilized ZrO 2 [8], Ni/10Sc 2 O 3 -1CeO 2 -89ZrO 2 [9,10], Ni/10 mol%Sc 2 O 3 -90 mol % ZrO 2 [10,11], and Ni/Zr 0.81 Sc 0.19 O 1.905 [12] have been reported. For the preparation of these electrode materials, the typical synthesis method involves using a solid state reaction.…”
Section: Introductionmentioning
confidence: 99%